$1.15 billion increase to approved for SAPT BG. Issue 41 (22nd October 2021) - Knopf, Alison
Abstract : The Substance Abuse Prevention and Treatment (SAPT) block grant (BG) is going to get an additional $1.15 billion, for a total of $3.008 billion, for FY 2022.